Cecal obstruction due to primary intestinal tuberculosis: a case series - Michalopoulos, Antonis (BioMed Central, 2011)
INTRODUCTION: Primary intestinal tuberculosis is a rare variant of tuberculosis. The preferred treatment is usually pharmaceutical, but surgery may be required for complicated cases. CASE PRESENTATION: We report two cases of primary intestinal tuberculosis where the initial diagnosis was wrong, with colonic cancer suggested in the first case and a Crohn's disease complication in the second. Both of our patients were Caucasians of Greek nationality. In the first case (a 60-year-old man), a right hemicolectomy was performed. In the second case (a 26-year-old man), excision was impossible due to the local conditions and peritoneal implantations. Histopathology revealed an inflammatory mass of tuberculous origin in the first case. In the second, cell culture and polymerase chain reaction tests revealed Mycobacterium tuberculosis. Both patients were given anti-tuberculosis therapy and their post-operative follow-up was uneventful. CONCLUSIONS: Gastrointestinal tuberculosis still appears sporadically and should be considered in the differential diagnosis along with other conditions of the bowel. The use of immunosuppressants and new pharmaceutical agents can change the prevalence of tuberculosis.